Life-cycle of Scinaia interrupta (Nemaliales, Rhodophyta) - León-Cisneros, Karla (2011)
The life-cycle of Scinaia interrupta (A.P. de Candolle) M. J. Wynne was investigated in vitro using four irradiance regimes: 4, 8, 12 and 16 μmol photons mˉ² sˉ¹. A triphasic heteromorphic life-cycle was observed. Carpospores released by cystocarps of gametophytes collected in the field developed into filamentous tetrasporophytes, which produced tetrahedral tetrasporangia. Tetrasporangial development was accelerated under higher irradiance levels. Tetraspores germinated into filamentous protonemal gametophytes, initially identical to the tetrasporophyte. Filamentous gametophytes developed apical utricles and gave rise directly to the fleshy gametophyte. Further development of the fleshy gametophyte was not observed at the lowest irradiance regime (4 μmol photons mˉ² sˉ¹). The present study reports for the first time the influence of the irradiance regime on the initial tetrasporangial development and in the development of the fleshy gametophyte, and reinforces the importance of light intensity on Scinaia life-cycle. Production of apical utricles by the filamentous gametophyte is newly reported for the genus.